원발성 섬모운동장애 - 조은혜; Eun Hye Cho (Laboratory Medicine Online, 15(1), 2025)
Primary ciliary dyskinesia (PCD) is a genetically heterogeneous disorder characterized by abnormal ciliary function, which may lead to health issues, including chronic respiratory infections, situs inversus, and infertility. This review aims to provide a comprehensive overview of the pathogenesis, clinical manifestations, diagnosis, and genetic basis of PCD. 원발성 섬모운동장애는 유전적으로 이질적인 질환으로, 비정상적인 섬모 기능으로 인해 만성 호흡기 감염, 내장역위증 및 불임을 초래한다. 본 고찰은 원발성 섬모운동장애의 발병 기전, 임상적 증상, 진단 및 유전적 기초에 대한 포괄적인 개요를 제공하는 것을 목표로 한다.